2018
DOI: 10.1080/14660970.2018.1432384
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholders’ understanding and perceptions of bio-banding in junior-elite football training

Abstract: The purpose of this study was to investigate the understanding and perceptions of professional football academy staff, youth players and parents/carers in the use of 'bio-banding' during a seven week, pre-season training period. Data included a series of one-to-one semi-structured interviews and semi-structured focus groups with the three participant groups. Data were collected at three distinct times: 1) pre-bio-banded training; 2) during-bio-banded training; and 3) post-bio-banded training. Data were analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 52 publications
5
39
0
Order By: Relevance
“…Also, recategorized athletes have also reported that development-based categorization methods provided more opportunity for them to engage key psychological constructs (Cumming et al, 2018 ), deemed important when assessing talent (Towlson et al, 2019 ). In addition, parents of recategorized athletes have stated that they trusted coaches to do what is right for their child's development and that such methods would not be adopted if the staff did not believe there was any value in doing so (Reeves et al, 2018 ). Apart from physical development, there may also be other reasons to reallocate players to a younger age group such as cognitive maturity that cannot be captured with this new method.…”
Section: Discussionmentioning
confidence: 99%
“…Also, recategorized athletes have also reported that development-based categorization methods provided more opportunity for them to engage key psychological constructs (Cumming et al, 2018 ), deemed important when assessing talent (Towlson et al, 2019 ). In addition, parents of recategorized athletes have stated that they trusted coaches to do what is right for their child's development and that such methods would not be adopted if the staff did not believe there was any value in doing so (Reeves et al, 2018 ). Apart from physical development, there may also be other reasons to reallocate players to a younger age group such as cognitive maturity that cannot be captured with this new method.…”
Section: Discussionmentioning
confidence: 99%
“…Bio-banding is suggested to be of most value at the onset of adolescence, when maturity selection biases begin to emerge. Additional to the physical and technical demands discussed within the current study, Reeves et al [1] state it is vital to consider the psychological and social impact of bio-banding. Cumming et al [5] found late developers possessed a psychological advantage characterised by greater self-regulation, the result of regularly competing against relatively older athletes in chronological competition.…”
Section: Discussionmentioning
confidence: 99%
“…The large variation in physical maturity between athletes undergoing puberty creates challenges within the talent identification process. Soccer clubs potentially overlook talented youth athletes because, in competition, the physically mature may stop technical skills emerging in the physically less mature [1]. To allow equal opportunity and reduce injury risk, many sports have grouped athletes by age and body mass [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The predicted mature stature (PMS) was the maturational indicator used to classify the judokas according to the maturational state. It has been used in investigations about the biological maturation effect on physical fitness of young people in general [38,41,42], in research focusing on youth performance in sport [43,44] and as a criterion for bio-banding in experimental training and tournaments [15][16][17] due to the advantages it presents compared to more valid but invasive indicators [45][46][47]. The PMS was calculated by the Khamis-Roche method [14].…”
Section: Methodsmentioning
confidence: 99%
“…The predicted mature status (PMS), a noninvasive method to estimate somatic maturity [14], is the most current method employed to assess maturity. Studies and implementations of bio-banding, on the other hand, are limited to the training or unofficial tournaments of young male soccer players [15][16][17].…”
Section: Introductionmentioning
confidence: 99%